Analisis Kebutuhan Pengembangan Buku Pendamping Berbasis Karakter Islam untuk Keterampilan Berbicara Bahasa Arab di SMP Islam Al Fahd Jakabaring - Kurniati, Depi; Harun, Muhammad; Lutfiyatun, Eka; Ramadhan, M. Rizky; Reza, Gita Marga; Maysya Ayu, Ghina (Ta'limi | Journal of Arabic Education and Arabic Studies, 2026)
This study investigates the need for developing an Islamic character–based supplementary book to improve Arabic speaking skills among students at SMP Islam Al Fahd Jakabaring, Palembang. The background of this research stems from the low communicative competence of students, which is influenced by grammar-dominated instruction and the limited availability of contextual learning materials.  The study aims to analyze students’ and teachers’ needs regarding the design of an Arabic supplementary book that integrates Islamic moral values into communicative speaking activities. A qualitative descriptive approach with a needs analysis design was employed. Data were obtained through observations, semi-structured interviews, and questionnaires. The data were analyzed thematically through stages of data reduction, display, and verification to identify key challenges and learning preferences. The findings show that students’ Arabic speaking ability remains at a low to moderate level. Most students can reproduce memorized dialogues but struggle to express ideas spontaneously. Teachers emphasized the absence of instructional materials that provide continuous speaking practice and moral integration. Students also demonstrated greater enthusiasm when learning activities were related to Islamic daily life contexts such as greetings, honesty, and politeness. These results indicate an urgent need for supplementary learning materials that combine linguistic development with Islamic character formation. In conclusion, this study highlights that integrating Islamic values into Arabic language learning materials not only strengthens students’ speaking competence but also supports their moral and spiritual growth. The findings provide a conceptual foundation for future development of value-based teaching resources that align linguistic goals with the broader mission of Islamic education.